The Oral health status of children with autism Spectrum disorder in KwaZulu-Nata, South Africa - Magandhree Naidoo; Shenuka Singh (BMC, 2018)
Abstract Background Echoing the sentiments of the Sixty-seventh World Health Assembly of May 2014, mandating the all-inclusive and synchronized efforts for the management of autism spectrum disorder (ASD), the aim of this current study was to investigate the oral health status of children with ASD aged between 7 to 14 years in KwaZulu-Natal, South Africa. Methods An investigative cross-sectional quantitative design employing non-probability purposeful sampling was conducted on 149 children with ASD attending special needs schools in KwaZulu-Natal. An intra-oral examination to investigate decayed, missing and filled teeth (DMFT/dmft), gingival index (GI), and plaque index (PI), attrition and soft tissue trauma using the World Oral Health Survey Form for Children, (2013) was implemented during data collection. Results Average DMFT/dmft scores of 3, 42 and 0, 97 were recorded respectively. Molars dominated the decayed component of the DMFT/dmft with an average caries prevalence of (51, 7% and 40, 8%) respectively. These results displayed zero fillings indicative of unmet treatment needs. The gingival index revealed mild gingival inflammation, (46, 3%) and the plaque index demonstrated visible plaque at (43, 6%).Attrition scores revealed mild loss of dental enamel (47%). The most prevalent soft tissue trauma recorded was lip biting (37, 25%). Conclusion Restorative or preventative treatment measures were not evident in this study. Unmet dental needs are therefore an important concern in this population. Health care planners should develop preventive programs targeted at high risk groups such as this study population.